Effect of room partitions on airborne and impact sound insulation in large, open rooms. Issue 1 (March 2016) - Zambon, Giovanni; Benocci, Roberto; Angelini, Fabio; Scrosati, Chiara
ISO 16283 for measuring sound insulation in buildings supersedes ISO 140 but is particularly lacking for measurements in large, open rooms of the type considered here (floor volume: 4000 m 3 ). Following ISO 16283-1, the room volume is theoretically divided into smaller volumes through an analysis of sound level distribution. Large absorbing panels in the ceiling prevent the growth of diffuse sound fields, and thus, the analysis makes critical use of normalization factors used in the airborne sound insulation and impact noise levels based on the Sabine equation. Given the likely division of finished floors into rooms, mobile separation walls are used here to investigate the influence of partitions on sound insulation. The results seem to show that they reduce sound insulation and increase impact noise level in each considered enclosed volume. These variations were investigated further through measurements taken in two volumes of different dimensions and at positions near to and far away from the separation walls.